Factors that influence students' interest in futsal material in elementary school learning: a cross-sectional study - Ma'arief, Moch. Andy Lukman; Muhammad, Heryanto Nur; Hartoto, Setiyo; Kogoya, Toni (Bima Loka: Journal of Physical Education, 2026)
This study aims to analyze the factors that influence students' interest in futsal material in elementary school learning. A cross-sectional design was used to examine the perceptions of 437 students in the city of Surabaya. Data collection used an interest questionnaire consisting of aspects of interest, attention, enjoyment, motivation, and participation. Questionnaire validity and reliability were established using Confirmatory Factor Analysis (CFA). The factors derived from student perceptions were analyzed using ANOVA (more than 2 groups) and independent t-tests (2 groups). All analyses were conducted using the Jamovi application at a significance level of 0.05. Independent t-test results revealed that gender significantly influences students’ interest levels (p < 0.05). ANOVA results demonstrated that grade level, students’ perceptions of futsal learning, parental support, and nutritional status were significantly associated with student interest (p < 0.05). School facilities, however, did not show a significant association (p = 0.256 > 0.05). These findings suggest that student interest is shaped by an interplay of individual and environmental factors. This study highlights the importance of enjoyment-based and adaptive instructional approaches that are responsive to students’ characteristics in fostering interest in futsal learning.